Utilização de domissanitários por moradores de áreas urbana e rural : uso e percepção - Trindade, Jaqueline Fernanda Souza (2023)
Household cleaning products are defined as substances or preparations intended for cleaning, disinfection or disinfestation at home, in collective and/or public environments, in places of common use and in water treatment. They include products for general cleaning and the like, products with antimicrobial action, biological products based on microorganisms, and disinfectant products. The use of disinfectant household cleaners to control pests in the domestic environment, such as cockroaches, ants and mosquitoes, and in gardening, has become popular and is becoming more present in the routine of Brazilians, leaving humans, animals and the environment susceptible to poisoning. Their use is associated with the perception that they are innocuous products, but they are the third class of agents that cause poisoning in Brazil. Thus, the objective was to investigate the use and risk perception of household cleaning products in urban and rural areas of the municipalities of Sinop, Sorriso and Lucas do Rio Verde. Data collection consisted of applying semi-structured questionnaires to buyers and sellers of household cleaning products in three agricultural stores in Sinop, two stores in Sorriso and two stores in Lucas do Rio Verde. The questionnaire had questions about the social profile, type of household cleaning recommended/purchased, mode and place of application, pest to be controlled, use of personal protective equipment (PPE) and possible cases of intoxication by the participant. The data showed that 81% of buyers of household cleaning products and 96% of salespeople in agricultural stores were male. About 71% of the participants declared that they intended the products for the urban area, demonstrating a greater perception of pests by the population in urban environments. Tradition was the point of greatest influence in choosing the agricultural store and effectiveness in choosing the disinfectant household cleaner. The trust of buyers towards the seller proved to be essential, influencing the final purchase decision, so it is necessary for sellers to know the products they sell in order to carry out the indications in the best way. Due to the perception of risk in the use of household cleaning products among the participants in this research, it was found that 64% performed the isolation of the places after application, 61.0% used some type of PPE during the applications and 63% stored the products in the outside homes or in isolated locations. The purchase of products with sales restrictions from institutions and specialized companies and the use of pest control products not indicated by the manufacturer were observed in this research. It also demonstrates the need for information and awareness programs about household cleaning products and the risks involved in their use, especially for sellers who sell and guide their use.